Development characteristics and field detection of overburden fracture zone in multiseam mining: A case study. Issue 3 (21st November 2019) - Tian, Chenglin; Liu, Yanbao; Yang, Xuelin; Hu, Qianting; Wang, Bo; Yang, Huiming
Abstract: During the multiseam mining process, the overlying strata were damaged due to different mining disturbances, where a large number of fractures were produced which were the main seepage paths of gas and water, easy to cause gas or water inrush accidents. Thus, it is necessary to explore the development characteristics of the fractured zone in the overlying strata from multiseam mining. In this paper, laboratory triaxial compression tests were firstly conducted on the rock specimens subjected to different mining disturbances. In these tests, the specimen was loaded to different stress before a regular test to simulate the different damage effects on the rock strata caused by different mining disturbances. And the corresponding values of m and s could be obtained through a calculation based on the test results. Subsequently, the numerical simulation was conducted to simulate the field situation, in which the m and s values were used in the numerical model combined with the Hoek‐Brown–modified criterion, and the results show that the overburden failure height was increased with the mining disturbances from 48 to 120 m, and then, the effects of mining height and interval thickness on the development height of fracture zone were studied by numerical simulation. Finally, the leakage of roof drilling at different stages was tested and calculated in the field. The results showed that the loss of leakage drilling can directly reflect the development degree of roof cracks, and the detection results were close to the development height of the numerical simulation fracture zone. It is verified that the simulation method used in this paper is feasible and can be used as a reference for similar research. Abstract : The mechanical parameters of rock strata with different damage degrees were obtained, and the relationship between multiple disturbances and surrounding rock damage was established; a method to simulate the development of fracture zone in multiseam mining was presented and verified by field detection.